Pengaruh Electronic Word Of Mouth (e-WOM) Terhadap Keputusan Pembelian Produk Somethinc Official Shop Di Shopee - Maulida Rahmi Nasution; Abdul Rasyid; Zuhriah Zuhriah (Journal of Creative Student Research, 2024)
Electronic Word of Mouth is a marketing communication strategy that helps consumers learn more about products they want to buy. This research uses central and peripheral routes based on Elaboration Likelihood Theory to determine the influence of Electronic Word of Mouth in the review column on purchasing decisions for Somehinc Official Shop products on Shopee. To conduct explanatory quantitative research, questionnaires were distributed to 271 respondents. The data analysis technique applied is multiple linear regression analysis. The results of this study are there is a significant effect partially between information relevance (X1), information accuracy (X2), value-added information (X3), and product ranking (X5) on purchasing decisions (Y), while the information quantity (X4) has no significant effect. However, there is a significant effect simultaneously between all dimensions of Electronic Word of Mouth on purchasing decisions (Y).